Sodium-23 Magnetic Resonance Imaging has potential for improving penumbra detection but not for estimating stroke onset time - (:unkn) unknown (My University, 2014)
Tissue sodium concentration increases in irreversibly damaged (core) tissue following ischemic stroke and can potentially help to differentiate the core from the adjacent hypoperfused but viable penumbra. To test this, multinuclear hydrogen-1/sodium-23 magnetic resonance imaging (MRI) was used to measure the changing sodium signal and hydrogen-apparent diffusion coefficient (ADC) in the ischemic core and penumbra after rat middle cerebral artery occlusion (MCAO). Penumbra and core were defined from perfusion imaging and histologically defined irreversibly damaged tissue. The sodium signal in the core increased linearly with time, whereas the ADC rapidly decreased by >30% within 20 minutes of stroke onset, with very little change thereafter (0.5–6 hours after MCAO). Previous reports suggest that the time point at which tissue sodium signal starts to rise above normal (onset of elevated tissue sodium, OETS) represents stroke onset time (SOT). However, extrapolating core data back in time resulted in a delay of 72±24 minutes in OETS compared with actual SOT. At the OETS in the core, penumbra sodium signal was significantly decreased (88±6%, P=0.0008), whereas penumbra ADC was not significantly different (92±18%, P=0.2) from contralateral tissue. In conclusion, reduced sodium-MRI signal may serve as a viability marker for penumbra detection and can complement hydrogen ADC and perfusion MRI in the time-independent assessment of tissue fate in acute stroke patients.
PUBLISHED
Keywords: Sodium MRI; Stroke Onset Time; Onset of Elevated Tissue Sodium; Penumbra; Neuroscience; Next Generation Medical Devices; ACUTE ISCHEMIC STROKE; MAGNETIC RESONANCE IMAGING; Medical Devices; Sodium-MRI